A Thematic Analysis of Customer Relationship Management Practices at Louis Philippe - Kritika Shamra; Jignesh Vidani (Journal of Advanced Research in Economics and Business Management, 2026)
Abstract This study aims to analyse the Customer Relationship Management (CRM) practices adopted by Louis Philippe at the Shyamal store through a qualitative thematic analysis approach. The primary objective of the research is to understand how CRM strategies help in building customer loyalty, enhancing customer satisfaction, and maintaining long-term relationships in the retail fashion industry. The study is based on an in-depth interview conducted with the store manager, and the collected qualitative data were analysed using NVivo software through thematic analysis techniques. The findings of the study identified major themes such as customer bonding and relationship building, personalised customer service, loyalty programmes, employee training and engagement, complaint handling mechanisms, and the use of digital CRM tools like Power App and Capillary Pro. The analysis revealed that effective customer interaction, personalised communication, and strong after-sales support significantly contribute to customer retention and repeat purchases. The study also highlighted the growing role of analytics and digital platforms in improving CRM efficiency in retail businesses. The research provides practical implications for retail organisations by emphasising the importance of customer-centric strategies, employee training, and technology-driven CRM systems for achieving sustainable competitive advantage and long-term customer loyalty. The study further contributes to qualitative CRM research through the application of NVivo-based thematic analysis techniques.